Coffee Shop Business Model Analysis - Budi Rahardjo; Rokhani Hasbullah; Fahim M Taqi (Fakultas Ekonomi, Universitas Bangka Belitung, 2019)
In line with the increase of coffee enthusiasts in Indonesia, coffee shops are now emerging roommates presents the enjoyment of local coffee in a distinctive way. One of the coffee shops that have a typical way is a Klinik Kopi. The purpose of this study: 1) to identify the Klinik Kopi business model, 2) to analyze internal and external factors that affect the Clinical Coffee business activities and, 3) to formulate strategies and improvement programs as the business development of the Klinik Kopi. This study uses a combination of business model canvas (BMC) approach and SWOT matrix analysis. Results of the study show that optimizing the main resources to create a new value proposition in designing future business models in the form of socio-entrepreneurship programs and business inspiration books influences every element of the business model canvas, namely an increase of carried out in key activities, key partners, channels, segments consumers and incoming revenue streams. Consumer relationships need to be improved in an effort to maintain customer segments.